Tinjauan Hukum Terhadap Persekutuan Komanditer Perbedaan Status dan Perilaku - Oktafianur, Muhammad Dodi; F, Ferdiyansyah; Warsito, Ronggo; Azizah, Tiara Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
A limited liability partnership is a form of business that involves members, namely the partners. These types of members have different roles and responsibilities in running the business. This paper aims to investigate the legal review of a partnership, focusing on the different status and behavior of a partnership. The research method used is legal document analysis, including applicable laws, relevant court decisions, as well as relevant legal literature. By using a descriptive-analytical approach, this research examines the roles, rights, and obligations of each member of a limited partnership in accordance with applicable legal regulations. The results show that the different status of a limited partnership is reflected in the rights and obligations they have. A limited partnership has more limited involvement in the management of the business and is liable only to the extent of their capital contribution.In the context of legal review, a clear understanding of the differences in the status and behavior of a limited partnership is crucial in determining their rights, obligations and responsibilities. The implications of this research can provide better guidance for parties involved in a limited partnership, both in the formation, management, and resolution of conflicts that may arise in the future.